Terminologization proper names (Eurasian Journal of Philology Science and Education, 2016)
An article gives a definition of term eponym which used in linguistics. It adduces some views of researchers upon diversity of eponyms. The article reports similarity between eponyms made from anthroponyms and onomastic lexica. It particularly points on the high similarity of eponyms with ethnonyms and lingvonyms. The article includes a list of eponyms applied in Modern Kazakh literature and linguistics. It has been explained in the article methods of formation, history of development, cultural and cognitive importance of some eponyms used in linguistics. The article contains brief descriptions referring to the foreign researchers’ articles of the last years and eponym vocabularies, and also there are references for some of them. In the end of the article author expresses his opinion in such way: collecting eponyms used in Turcology, and drawing up vocabularies and use them efficiently in scientific purposes are the most important index of determining the significance of Turkic language people referring to the whole humanity’s culture and science.
Keywords: Кazakh linguistics; Turkic languages; terminological Ka¬zakh language; eponym; a term; onomastics